MODERN TRENDS AND CHALLENGES IN INTERNATIONAL MANAGEMENT: STRATEGIC APPROACHES TO ADAPTATION IN CONDITIONS OF GLOBAL UNCERTAINTY - OLIINYK, Victoriia; YEFREMOV, Illia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Modern international management is under the constant influence of globalization and internationalization, which change the nature of doing business, expand the geography of markets and increase the importance of intercultural cooperation. In the conditions of global uncertainty, enterprises face numerous challenges that require managers not only to have high professional training, but also to be able to adapt strategies under the influence of external and internal factors. Management systems and business practices in different countries differ significantly, as they are formed under the influence of cultural, economic and social conditions. The identification and research of the main approaches to management in the international context, in particular such paradigms as Japanese, American and European, allows to better understand the ways of adapting companies to the changing conditions of the world economy. In particular, the Japanese model focuses on collectivism and long-term loyalty, the American model on individualism and a technocratic approach, and the European model on social protection and a harmonious combination of rationality and cultural characteristics. The article examines current trends and challenges in international management under conditions of global uncertainty. The analysis of major management paradigms—Japanese, American, and European—provides insights into the differences in management approaches based on collective and individual values, social responsibility, competition levels, and corporate culture. Significant attention is given to the adaptation of management practices to rapidly changing external conditions, including digital innovations and the assurance of economic, social, energy, and financial security. The Ukrainian management paradigm, influenced by globalization and national specifics, seeks to find its unique path by combining elements of paternalism and initiative to enhance the resilience and competitiveness of enterprises in the international market. The research results highlight the necessity of a strategic approach that considers each market’s specificity, cultural differences, and management flexibility, enabling an effective response to challenges and adaptation to new conditions within the global economy.